Neuromyelitis optica presenting as acute bilateral ptosis. Issue 1 (25th November 2016) - Joshi, Purwa; Lanford, Jeremy; Bourke, David
Abstract : Acute bilateral ptosis can be a hallmark of several serious neurological conditions. We present the first case of acute bilateral near-complete ptosis secondary to neuromyelitis optica spectrum disorder. We suggest that clinicians should consider this disorder among the differential diagnosis of acute bilateral ptosis, especially if there are other brainstem signs.